Answer:
your equation is wrong!! the answer is [tex]10[/tex]
Step-by-step explanation:
the correct order of the equation is:
[tex](2-3)(-1)-(-3)(3)[/tex]
first, solve in the parentheses from left to right:
[tex](2-3)(-1)-(-3)(3)=\\(-1)(-1)-(-3)(3)=\\1-(-3)(3)=\\[/tex]
If we have 2 negative signs then we will change them to positive :
[tex]1-(-3)(3)=\\1+3(3)\\[/tex]
now we have an equation with parentheses, we will multiply [tex]3(3)\\[/tex] because the parentheses go first.
[tex]1+3(3)=\\1+9=10[/tex]